2017
DOI: 10.4322/acr.2017.029
|View full text |Cite
|
Sign up to set email alerts
|

Native-valve endocarditis caused by Achromobacter xylosoxidans: a case report and review of literature

Abstract: Achromobacter xylosoxidans is a Gram-negative aerobic bacterium first described by Yabuuchi and Ohyama in 1971. A. xylosoxidans is frequently found in aquatic environments. Abdominal, urinary tract, ocular, pneumonia, meningitis, and osteomyelitis are the most common infections. Infective endocarditis is rare. As far as we know, until now, only 19 cases have been described, including this current report. We report the case of community-acquired native valve endocarditis caused by A. xylosoxidans in an elderly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
15
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 27 publications
0
15
0
Order By: Relevance
“…To date, only 20 cases ( Table 1 ) of A. xylosoxidans endocarditis have been reported in the literature, of which only two involved a native valve [ 8 – 28 ]. Considering the treatment and outcome: 11 of 19 (58%) required surgical intervention; 8 of 17 (47%) died, 2 of the 8 deaths (22%) were from the operated group and the other 6 (75%) were from the clinically treated group [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…To date, only 20 cases ( Table 1 ) of A. xylosoxidans endocarditis have been reported in the literature, of which only two involved a native valve [ 8 – 28 ]. Considering the treatment and outcome: 11 of 19 (58%) required surgical intervention; 8 of 17 (47%) died, 2 of the 8 deaths (22%) were from the operated group and the other 6 (75%) were from the clinically treated group [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…For instance, some studies have indicated that Klebsiella was enriched in cancer and diabetes patients [44], and be related to various infectious diseases [45] and neurosurgery disease [14]. Furthermore, Achromobacter was also reported to be related to human diseases such as pneumonia [46], colitis [47], cancer [48], and cardiovascular diseases [13]. All of the findings, as mentioned above, were also linked with positive correlations between the abundances of these opportunistic pathogens and human disease-related pathways in our study.…”
Section: Opportunistic Pathogens Associated Human Disease-related Patmentioning
confidence: 99%
“…These opportunistic pathogens are ubiquitous in the environment and are known to be considered as commensal in the human gut; but the increasing numbers of their population could be a significant risk factor for the infection [11,12]. Moreover, these opportunistic pathogens are prominently linked with human diseases such as pneumonia, colitis, cancer, diabetes, neurosurgery, and cardiovascular diseases [13,14].…”
mentioning
confidence: 99%
“…infection are in fact at greater risk of experiencing a pulmonary exacerbation (9), and patients with chronic infections exhibit severe airway obstruction and more rapid lung function decline (13-15). Further, these pathogens can cause a range of serious diseases such as pneumonia, meningitis, osteomyelitis, urinary tract infections, and ocular infection in non-CF patients (16). Therefore, early and correct identification of Achromobacter spp.…”
Section: Introductionmentioning
confidence: 99%